Actualization of the Spirit of Nationhood in Karawitan Musical Compositions by Balinese Maestro I Wayan Beratha - I Gede Yudarta; Ni Luh Sutjiati Beratha; I Komang Sudirga (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Like other art forms, dance and music serve as expressive media for conveying social messages, including nationalism. However, nationalism in musical rhythms is often less explicit than in verbal or visual arts. This article explores the actualization of the spirit of nationhood in dance and karawitan—traditional Balinese musical compositions—by I Wayan Beratha (1926–2014), a maestro who created over 50 works, including dance pieces and instrumental compositions inspired by the national spirit of their time. Using a qualitative approach, this study gathers data through literature reviews, document analysis, and in-depth interviews. Ricoeur’s hermeneutical theory informs the analysis, positioning texts as a foundation for interpreting their social and ideological contexts. Findings reveal that Beratha’s works embody ideological themes, creative expression, and a deep commitment to national unity. His contributions continue to inspire contemporary artists, encouraging them to preserve and expand upon his legacy.